2020
DOI: 10.1111/1756-185x.13864
|View full text |Cite
|
Sign up to set email alerts
|

Work disability in rheumatic diseases: Baseline results from an inception cohort

Abstract: Aim: We aimed to characterize work disability in patients with newly diagnosed rheumatic diseases and compare work characteristics between patients with rheumatic diseases and controls without rheumatic diseases at diagnosis. Methods: Patients with inflammatory arthritis (IA) and osteoarthritis (OA), surrogates for autoimmune and non-autoimmune rheumatic diseases, respectively, and controls of working age were surveyed at diagnosis. Patients with rheumatic diseases who were employed before symptom onset were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
11
1
1
Order By: Relevance
“…Both groups had a lower WAI-score at three and six month follow-up compared to baseline but the changes were small and not statistically signi cant. The scores on WAI in this study are comparable (5,16) or higher (41) than the scores reported in previous studies on working OA-populations, indicating less possibility for improving the score on WAI.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Both groups had a lower WAI-score at three and six month follow-up compared to baseline but the changes were small and not statistically signi cant. The scores on WAI in this study are comparable (5,16) or higher (41) than the scores reported in previous studies on working OA-populations, indicating less possibility for improving the score on WAI.…”
Section: Discussioncontrasting
confidence: 46%
“…Osteoarthritis (OA) is a common musculoskeletal disorder (1) affecting both individuals and the society at large (2,3). OA often leads to pain, disability and reduced quality of life (2,4) which have been shown to affect work ability (5) and productivity (6) with presenteeism (reduced work capacity) being more common than absenteeism (7)(8)(9). In a large population-based cohort study conducted in Sweden, individuals with knee OA had an almost two-folded risk of sick leave and 40-50 % increased risk of disability pension in comparison with the general population (10).…”
Section: Introductionmentioning
confidence: 99%
“…A sample size calculation was made using the primary outcome variable work ability measured with WAI to determine the required number of participants with a power of 80% and a two-tailed significance level of 0.05. Effect sizes (between group differences) for WAI were pragmatically based on SD on WAI from previous studies [ 5 , 41 ] with the approximation of 0.45 SD as the minimal clinically important difference [ 42 ]. The sample size calculation yielded approximately 80 participants per group.…”
Section: Methodsmentioning
confidence: 99%
“…Osteoarthritis (OA) is a common musculoskeletal disorder [ 1 ] affecting both individuals and the society at large [ 2 , 3 ]. OA often leads to pain, disability and reduced quality of life [ 2 , 4 ] which have been shown to affect work ability [ 5 ] and productivity [ 6 ] with presenteeism (reduced work capacity) being more common than absenteeism [ 7 9 ]. In a large population-based cohort study conducted in Sweden, individuals with knee OA had an almost two-folded risk of sick leave and 40–50% increased risk of disability pension in comparison with the general population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with pain, stiffness, swelling, fatigue, and sleeping problems [5], having a debilitating effect on functionality. RA is also associated with cachexia [6], low quality of life (QoL) [7,8], limitations in everyday life [9,10], lower work ability [11,12], and sexual problems [13].…”
Section: Introductionmentioning
confidence: 99%